Optimizing Recruitment and Retention in Cancer Clinical Trials in Low-Resource Settings: Barriers and Facilitators From Nigerian Provider's Perspectives - Babayemi O. Olakunde; Ngozi Idemili-Aronu; Tara M. Friebel-Klingner; Adaeze Chike-Okoli; Ijeoma U. Itanyi; Tonia C. Onyeka; Kimberly Levinson; Anne F. Rositch; Richard B.S. Roden; Tzyy-Choou Wu; Echezona E. Ezeanolue (JCO Global Oncology)
PURPOSEThe under-representation of African countries in cancer clinical trials continues to widen the cancer health disparity. In this study, we assessed health care workers' perspectives on recruitment and retention in cancer clinical trials in Nigeria.METHODSThis study was a convergent parallel mixed-methods design, using a survey for quantitative analysis and focus group discussions (FGDs) for further qualitative investigation. The health care providers that participated in the study were drawn from the ICON-3 Practice-based Research Network across the six geopolitical zones in Nigeria.RESULTSOf the 42 providers, 35 completed the survey and 25 participated in the FGDs. The most cited (agreed or strongly agreed) patient-related barriers were lack of understanding of cancer clinical trials (83%), cultural barriers (77%), and lack of financial compensation for study visits (77%). The most cited provider-related barriers were negative attitude of the clinical team (89%), lack of training in good clinical practice (89%), and an overwhelming clinical workload (86%). On trial-related barriers, about 71% agreed or strongly agreed that lack of trial publicity was a barrier. Over 90% of the respondents agreed or strongly agreed that several factors, including the friendliness of the study team (97%) and clarity in the presentation of trial information (97%), are important facilitators. The FGDs unveiled additional themes, including systems-related barriers such as lack of infrastructure, limited research collaboration, and prolonged ethical approval process, and capacity building and community engagement as potential facilitators.CONCLUSIONOur study provides providers' perspectives on the barriers and facilitators to the recruitment and retention of participants in cancer clinical trials in a low-resource setting and highlights the need for culturally appropriate recruitment strategies.